O diálogo entre cultura escolar e cultura popular na educação de jovens e adultos e numa Escola de Guanambi (BA) - Maria de Fatima Pereira Carvalho (2013)
This research The dialogue between school culture and popular culture in youth and adult education (YAE) in a school in Guanambi (BA) aimed to investigate and describe the YAE Cultural Nights in Guanambi/ BA. We identified the characters; what motivates them to participate in the event; and how they evaluate it. Beyond this, we tried to assess the educational role of these practices and the dialogue established between school culture and popular culture. In order to comprehend the data, we based on qualitative approach assumptions. From the technical and methodological standpoint, we used the field diary. It was made from observations in YAE classes in the school, locus of this research, educators' planning meetings which let us observe the activity construction process. We also interviewed eight students, two teachers, one YAE teaching coordinator, a manager and a coordinator of the studied school. Then, it was possible to observe how the dialogue between popular culture and school culture occurs in the activity that is the object of this study. In the reviewed literature that discuss this issue, we highlight Arroyo (2001, 2005, 2006, 2007, 2011), Bosi (1992), Brandão (1984, 1989, 2002, 2004, 2009) Canclini (1998), Dayrell (1996), Forquin (1993), Freire (1969, 1979.1987, 1989, 1996) Haddad (2007) Hernandez, (1998), Laraia (2006), Soares and Favero (2009) among others. In summary, we noticed a certain distance between popular culture and school culture in YAE, as we attested in the analysis of the dialogues among students, teachers, coordinators, managers, and etc. Therefore, this dissertation points out the need for a curricular organization that addresses the peculiarities of YAE.